Morphology-based Selection, Metabolic Profiling and Omics Technology Compared with the Classical Morphology-based Embryo Selection in In-Vitro Fertilization - Ria Margiana (Journal of Global Pharma Technology, 2018)
Introduction: The medical industry is one of the dynamic industries with frequent innovations and discoveries, which in-vitro fertilization (IVF) technology being the recent change. IVF is an assisted reproductive technology that was invented to treat fertility and genetic problems associated with conception which involves implantation of good quality embryosin to uterus. The success of IVF depends majorly on the embryo selection, the age of the gestational carrier and the cause of infertility. In IVF, more than one embryo can be implanted in uterus, which may result in multiple pregnancies about 30% of embryo resulting from IVF treatments have abnormal chromosome, and this percentage may rise up to 60% with poor embryo selection. This has led to many studies in the last decade on possible methods to replace the conventional morphological evaluations or complement with them. This paper, therefore, aims to assess the performance of morphology-based selection, metabolic profiling, and omics technology in IVF procedure when compared with the modern selection methods. Method: This study provides a review of literatures on the assessment of the effectiveness of the traditional embryo transfer methods when compared with the modern methods. The review was based on Pub Med electronic database. Information on female patient, different intervention models, comparisons and study designs was also provided. Results: Out of the 58 studies that were evaluated, only ten were identified as eligible for the review because they provided substantial reports on morphology assessment, metabolic profiling, and omics technology. The selected articles proved to be significant since they provided a comparative analysis of the models and their outcomes.  This review identified that the modern methods had positive results as opposed to the traditional methods that had less positive results.  Conclusion: Modern methods have positive results due to their precision compared to morphological technique. The time lapse imaging technique has the highest accuracy, and it complements the morphological method by reducing chances of failure of implantation caused by exposing the embryo to conditions outside the incubator.  Results from the other modern method including metabolic profiling, omics technology, whether they had lower pregnancy rates and significant implantation failure or not. From the results, one can judge that morpho kinetics is the best model due to its high precision.  On the integration of the time-lapse technique with classical morphology assessment, there was no significant difference between the time-lapse technique and the morphology evaluation. Although morph kinetics provides high-quality results, the traditional methods are continually being used because they provide an observational assessment of the embryo cells. Also, the morphology-based method issued worldwide due to the lack of consensus on the benefits of the novel embryo transfer techniques.Keywords: Morphology-based selection, Metabolic   profiling, Omics technology, In-vitro fertilization